From the Ground Up, Again: An Interview With Michael League - League, Panayotis (Critical Studies in Improvisation / Études critiques en improvisation, 2021)
Michael League (Snarky Puppy), here interviewed by Panayotis League, offers a frank assessment of the new economic realities for working musicians. He notes that even before the pandemic, digital streaming services such as Spotify had all but eliminated recordings as an income source for musicians. COVID-19 has now decimated their other primary revenue stream: live shows.